Sustainability in Environmental Engineering and Science Select Proceedings of SEES 2019 - Kumar, Sunil; Kalamdhad, Ajay.; Ghangrekar, Makarand M.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2021)
This book consists of select peer-reviewed papers from the International Conference on Sustainable Environmental Engineering and Science (SEES) 2019. The main focus of the book is to propose sustainable technologies to address the growing environmental challenges. The contents cover several topics of relevance such as air pollution, solid waste management, wastewater treatment, industrial pollution, and suggests eco-friendly and cost-effective techniques to tackle them. Given the range of topics covered, the book will be useful to researchers and professionals working in the multidisciplinary area of sustainability. .
Chapter 1: Design & Simulate of Vertical Handover Algorithm for Intelligent Transport System Using Analytic Hierarchy Process -- Chapter 2: Particulate Matter Emission Assessment and Future Outlook through Air Dispersion Model for Sustainable Development Planning in an Inland City in Central Maharashtra, India -- Chapter 3: Strategies on implementation of anaerobic digestion for circular economy in India -- Chapter 4: Sensitivity study on the classical biofilm model using a simplified solution method -- Chapter 5: Risk of extinction of species in an ecological system: estimation and analysis -- Chapter 6: Brassica juncea (L.)Czern. (Indian mustard): A potential candidate for the phytoremediation of mercury from soil -- Chapter 7: Stabilization of Expansive Soil Using Saw Dust -- Chapter 8: Analysing the Influence of Groundwater Exploitation on Its Quality in Kolkata -- Chapter 9: Efficacy evaluation of conventional water treatment process and THMs modeling in drinking water of five cities in India -- Chapter 10: Study of Water Quality Index to ascertain the suitability of surface water for domesticpurposes -- Chapter 11: Evaluation of anthropogenic driven water pollution effects in an urban freshwater resource using Integration Pollution Index Method -- Chapter 12: Improved Sequential Approach for Hybrid Bioleaching of Metals from E-Waste -- Chapter 13: Green Energy Based Low Cost Smart Indoor Air Quality Monitoring And Purifying System -- Chapter 14: Degradation of phenol using batch-fluidization process by transition metal impregnated red mud as modified catalyst in heterogeneous Fenton process -- Chapter 15: Application of low-cost air quality monitoring sensor to assess the exposure of ambient air pollution due to PM2.5 and PM10 -- Chapter 16: Estimation of Green House Gases in the Ambient Air.
Keywords: Environmental sciences; Waste management; Air pollution; Water pollution; Pollution prevention; Renewable energy resources; Environmental Science and Engineering; Waste Management/Waste Technology; Atmospheric Protection/Air Quality Control/Air Pollution; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Industrial Pollution Prevention; Renewable and Green Energy